PENGARUH PERMAINAN JEMBATAN PELANGI TERHADAP KEMAMPUAN SAINS PERMULAAN ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA 1 PEKANBARU - Rahmawati Rahmawati; Wusono Indarto; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on observations in the field it can be seen that the science ability of children aged 4-5 years has not developed optimally. So the need to use a rainbow bridge game. This observation aims to determine the influence of the rainbow bridge game on the early science skills. This observation is done in TK Pembina 1 Pekanbaru. This observation use experiment method with design one group pre-test post-test design with total samples 21 childrens. Data collection techniques used are observation. Data analysis techniques use t-test with use spss programme windows version. 20. Results of data analysis obtained t arithmetic = 2,086 with sig. 0,00 < 0,05. It can be concluded that there are differences in early sciene skills before and after the rainbow bridge game. The effect given by the rainbow bridge game is based on the formula N gain of 61,15%.Keywords: Early Science, Rainbow Bridge Game